EFFECTS OF PLANT-BASED DIETS ON CARDIOVASCULAR RISK - Polianska, O. S.; Rusnak, I. T.; Hulaha, O. I.; Horobets, K. V.; Kulachek, Ya. V.; Moskaliuk, I. I. (Rehabilitation and Recreation, 2023)
Metaboloc diseases such as coronary heart disease, stroke, obesity, and type 2 diabetes mellitus, represent a significant burden on life, health, and the economy. About half of the deaths from cardiovascular disease caused by metabolic disorders could be prevented by the correction of nutrition. Plant-based (vegetarian and vegan) diets (PBD) are an effective method for improving nutrient absorption. The purpose of the present study is a theoretical analysis and generalization of literary sources justifying the use of various diets in cardiovascular diseases (CVD). Research material and methods. In this review, we have explored the most recent literature data on the effect of a PBD on the risk of development, course, and complications of CVD, with a particular focus on systematic reviews and meta-analyses, especially those based on randomized clinical trials. Results from observational studies were included as supporting evidence. Results of the research. An analysis of the literature strongly suggests that plant-based diets can reduce the risk of CVD by approximately 40%, and the risk of cerebrovascular disease by 29%. PBD also cut the risk of developing metabolic syndrome and type 2 diabetes by about half. Well-planned PBD are beneficial and effective for weight and glycemic control, and provide metabolic and cardiovascular benefits, including reductions in blood lipids and blood pressure. Several possible mechanisms may explain the beneficial metabolic effects of PBD: decreased caloric intake, increased fiber intake, decreased saturated fat and cholesterol intake, increased polyunsaturated and monounsaturated fatty acid intake, increased antioxidant and micronutrient intake, increased plant protein and sterols intake. Conclusions. PBD are an effective means of prevention and treatment of metabolic diseases, cardiovascular pathology, as they show effectiveness in normalizing blood pressure and indicators of atherogenesis. The use of PBD as a method of prevention and treatment of metabolic diseases should be promoted for patients with CVD.